Feasibility trial of GP and case-managed support for workplace sickness absence. Issue 3 (10th April 2013) - Rannard, Anne; Gabbay, Mark; Sen, Dil; Riley, Richard; Britt, David
Abstract : Aim: Our aim was to compare the return-to-work rates between individuals supported by their GP plus workplace health advisers (intervention group) and those supported by their GP alone. Background: Workplace sickness absence places a significant cost burden on individuals and the wider economy. Previous research shows better outcomes for individuals if they are supported while still in employment, or have been on sick leave for four weeks or less. Those helped back to work at an early stage are more likely to remain at work. A non-medicalised case-managed approach appears to have the best outcomes and can prevent or reduce the slide onto out-of-work benefits, but UK literature on its effectiveness is sparse. Methods: The design was a feasibility-controlled trial in which participants were sickness absentees, or presentees in employment with work-related health problems. Individuals completed health status measures (SF-36; EQ-5D) and a Job Content Questionnaire at baseline and again at four-month follow-up. Findings: In the intervention group, 29/60 participants completed both phases of the trial. GP practices referred two control patients, and, despite various attempts by the research team, GPs failed to engage with the trial. This finding is of concern, although not unique in primary care research. In earlier studies, GPs reported a lack of knowledge and confidence in dealing with workplace health issues. Despite this, we report interesting findings from the case-managed group, the majority of whom returned to work within a month. Age and length of sickness absence at recruitment were better predictors of return-to-work rates than the number of case-managed contacts. The traditional randomised controlled trial approach was unsuitable for this study. GPs showed low interest in workplace sickness absence, despite their pivotal role in the process. This study informed a larger Department for Work and Pensions study of case-managed support.